Impact of routine reporting of estimated glomerular filtration rate using the CKD‐EPI formula in a community population: A cross‐sectional cohort study. Issue 9 (September 2014) - Mitchell, Tim; Hadlow, Narelle; Chakera, Aron
Abstract Aim Most laboratories are moving to report estimated glomerular filtration rates (eGFR) using the Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) formula. However, data on the prevalence of chronic kidney disease (CKD) in the population and its economic impact have to date been modelled using data derived from the modification of diet in renal disease (MDRD) equation. Evaluating the impact of CKD‐EPI on prevalence has important implications for referral patterns and health expenditure. Methods eGFR were calculated from 2 295 313 creatinine results from 833 334 patients using the MDRD and CKD‐EPI formulae. The proportion of patients in each CKD stage was determined and annual rates of change of eGFR in patients assigned to a new CKD stage compared with their previous CKD stage calculated. The effects of age on eGFR were assessed. Results Reporting of eGFR using the CKD‐EPI equation reduced the prevalence of CKD stages III‐V from 9.2% to 7.6%. A total of 181 126 patients were reclassified using CKD‐EPI with 171 298 changing to a better CKD stage. Reclassification rates were highest in CKD stages II and III. Patients reclassified from stage III to II tended to be younger or female. eGFR declines rapidly after the age of 60. Conclusions Introduction of routine eGFR reporting using the CKD‐EPI formula will reduce the population prevalence of CKD. CKD‐EPI reporting better identifies patients at risk of further decline in renal function. Improvement in the classification should reduce unnecessary costs related to surveillance and referral. The impact of ageing on renal function should be appreciated.